Towards a definition of Mediterranean Noir or Crime in the Mediterranean: Mediterranean noir or Mediterranean crime fiction? - Barbara Pezzotti (Belphégor)
This article argues that Mediterranean crime fiction is not simply a subgenre that showcases criminal organisations and beautiful landscapes, but also a formulation that overcomes the exclusionary European borders, and makes the “parent” label Euronoir more inclusive. In order to prove this point, this article analyses Andrea Camilleri’s Il ladro di merendine (1996) and Jean Claude Izzo’s Total Khéops (1996) through the lens of transculturality (Welsch) and the idea of “third space” (Bhabha). It shows how, with their reference to a common Mediterranean culture and history, these novels shape transcultural spaces where human beings coexist and adapt to each other. Both novels make use of the concept of “homecoming” as a counter-narrative for the present anti-immigration rhetoric, and represent the Mediterranean as a Mare Nostrum which, according to Paolo Rumiz’s formulation, is a space shared by those who inhabit it, where inhabiting does not necessarily coincide with belonging or possession1. In doing so, Il ladro di merendine and Total Khéops represent Mediterranean cities as places where the encounter supersides conflict, overcoming the exclusionary mechanisms of the nation-state.